Effects of Cold Saline Solution Infusion on Cooling Performance with Endovascular Therapeutic Hypothermia - Dallan, Luis Augusto Palma; Dae, Michael; Giannetti, Natali Schiavo; Polastri, Tathiane Facholi; Rochitte, Carlos Eduardo; Hajjar, Ludhmila Abrahao; Martin, Claudia Yanet Bernoche San; Lima, Felipe Gallego (Cardiology and Cardiovascular Medicine, 2020)
Background: Therapeutic hypothermia (TH) reduces the damage by ischemia/reperfusion cell syndrome in cardiac arrests, however, the role of cold saline as an adjuvant therapy to endovascular cooling in STEMI remains controversial. The aim was the evaluation of cold saline infusion versus no cold saline concomitant to endovascular cooling in the development of a TH protocol in STEMIs. Methods: Patients within the 6h onset of chest pain, presenting anterior or inferior STEMIs. TH induced through the Proteus® Endovascular System implant, by cooling for 18 minutes before coronary recanalization at the target temperature of 33±1.0°C before PCI. Patients were randomized to the administration of 1L cold saline solution at 1-4°C (CSS) versus no cold saline solution (NCSS). The primary endpoint was lower temperature by the opening of the vessel through primary PCI. Results: TH was successfully induced in 10 patients – 5 in the CSS group and 5 in the NCSS group. After 18 minutes of TH, all patients (100%) had already achieved core temperature <35ºC, and 90% of them within the pre-specified 33.0 ± 1.0ºC target temperature. In the CCS group, all five patients (100%) reached the target temperature, as compared with four patients (80%) in the NCCS group. The mean temperature reached was 33.0ºC (± 0.6) in the CCS group as compared to 33.3ºC (± 0.8) in the NCCS group (p=0.59), thus 0.3ºC lower temperature by the time of balloon angioplasty favoring the CSS group as compared with the NCSS group. After 30 min, the mean temperature was 32ºC (± 0.4ºC) in the CCS and 32.4ºC (± 0.5ºC) in the NCCS group (p=0.12). The MACE rates were similar between both groups (p=ns). Conclusions: We conclude that when using more powerful endovascular cooling